Insights of Square Toiletries Limited call center operations and how it should be bestowed to infer result driven marketing decisions for brand promotion - Khan, Iffatur Rahman (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.